2012
DOI: 10.1186/1476-511x-11-93
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Samsum ant (Pachycondyla sennaarensis) venom against lipopolysaccharides through antioxidant and upregulation of Akt1 signaling in rats

Abstract: BackgroundThis study aimed at investigating the oxidative stress ameliorating effect, lipids profile restoration, and the anti-inflammatory effect of Samsum Ant Venom (SAV) in induced endotoxemic male rats, injected with bacterial lipopolysaccharides (LPS).ResultsResults revealed that LPS significantly increased the oxidative stress indications in LPS-injected rats. A significant increase of both malondialdehyde (MDA), and advanced oxidative protein products (AOPP), as well as a significant suppression of glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…We found that the level of MDA was elevated in diseased rats while, SAV restored the oxidative markers in these rats. Previous studies have shown that SAV plays an active role in scavenging free radicals [26]. Indeed, a significant enhancement of glutathione and catalase was observed in the SAV supplemented rats in this study.…”
Section: Discussionsupporting
confidence: 72%
“…We found that the level of MDA was elevated in diseased rats while, SAV restored the oxidative markers in these rats. Previous studies have shown that SAV plays an active role in scavenging free radicals [26]. Indeed, a significant enhancement of glutathione and catalase was observed in the SAV supplemented rats in this study.…”
Section: Discussionsupporting
confidence: 72%
“…Our previous work based on the proteins derived from camel milk have demonstrated their enhanced wound healing capacity in diabetic as well as older animals [ 13 15 ]. Additionally, our recent study [ 16 ] revealed the ability of this protein to direct immune processes and its ability to trigger the proliferation of peripheral blood mononuclear cells (PBMCs) [ 17 ]. In the present piece of work, we hypothesize that wound healing in diabetic animals could be improved by supplementing camel milk derived protein fractions.…”
Section: Introductionmentioning
confidence: 99%
“…The limited work done thus far reveals that ant venoms show enormous chemical diversity comprising alkaloids, hydrocarbons, proteins and peptides 3,4 . Most studies on ant venoms have focused on the alkaloidal components, as these are a major cause of allergic reactions due to their histamine-releasing properties 13,14 . However, more recent studies have shown the involvement of the proteome in eliciting these allergic 15,16 and antiinflammatory 17,18 properties.…”
Section: Introductionmentioning
confidence: 99%